1995
DOI: 10.1038/bjc.1995.349
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in diagnosis have changed the incidence of histological types in advanced gastric cancer

Abstract: SummaryThe data on 912 patients with early cancer and 1245 with advanced cancer who were seen between 1971 and 1990 were compared. The incidence of undifferentiated-type cancer increased significantly in patients with advanced gastric cancer, but not in patients with early gastric cancer. When the histological types were compared with regard to sex, age and location in patients with early gastric cancer the undifferentiated type was found to increase only in males, while in patients with advanced gastric canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
8

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
8
0
8
Order By: Relevance
“…However, the decline in the diffuse type has been more gradual. In some series, although intestinal type gastric cancer remained the predominant subtype, the relative proportion of diffuse type cancer became higher over the course of time, (23)(24)(25)(26)(27) but this is not noted in all studies. (28,29) The reasons for this relative increase in the proportion of diffuse type cancer are speculative.…”
Section: Clinical Epidemiology Of Gastric Cancermentioning
confidence: 99%
“…However, the decline in the diffuse type has been more gradual. In some series, although intestinal type gastric cancer remained the predominant subtype, the relative proportion of diffuse type cancer became higher over the course of time, (23)(24)(25)(26)(27) but this is not noted in all studies. (28,29) The reasons for this relative increase in the proportion of diffuse type cancer are speculative.…”
Section: Clinical Epidemiology Of Gastric Cancermentioning
confidence: 99%
“…On the other hand, the decline in the diffuse type has been more gradual. Consequently, the diffuse type represents about 30 percent of gastric carcinoma [8].…”
Section: Distribution Of Histologic Typesmentioning
confidence: 99%
“…Some studies have reported an increase in the diffuse type of gastric carcinoma, especially the signet-ring cell type [6] . As a result, the diffuse type now accounts for about 30% of gastric carcinomas in some reported series [7] . Intestinal-type and diffuse-type gastric cancer differ in their epidemiology, pathogenesis, genetic profile, and clinical outcome [8] .…”
Section: Introductionmentioning
confidence: 99%